2013
DOI: 10.3892/ijmm.2013.1451
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC inhibitor, panobinostat, induces apoptosis by suppressing the expresssion of specificity protein 1 in oral squamous cell carcinoma

Abstract: Inhibitors of histone deacetylases (HDACs) represent a novel class of therapeutic anticancer agents. Panobinostat (LBH589) induces apoptosis through the regulation of specificity protein 1 (Sp1) in the oral squamous cell carcinoma (OSCC) cell lines, HN22 and HSC4. In this study, we analyzed the underlying signaling pathways and the mechanisms involved in this process by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay, 4' ,6-diamidino-2-phenylindole (DAPI) st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…In addition to modifying histone acetylation status, HDACs have numerous other nonhistone targets, including proteins involved in transcription regulation, cell proliferation, metabolism, apoptosis, and immune response (70). HDAC inhibitors have been shown to alter the expression level and function of cellular proteins p21, E2F1, and SP1 (71)(72)(73)(74), all of which can impact upon optimal viral gene expression and growth. The transcription factors E2F1 and SP1 both play a role in transcriptional control of E1A (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to modifying histone acetylation status, HDACs have numerous other nonhistone targets, including proteins involved in transcription regulation, cell proliferation, metabolism, apoptosis, and immune response (70). HDAC inhibitors have been shown to alter the expression level and function of cellular proteins p21, E2F1, and SP1 (71)(72)(73)(74), all of which can impact upon optimal viral gene expression and growth. The transcription factors E2F1 and SP1 both play a role in transcriptional control of E1A (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, treatment of OSCC cells (HN22 and HSC4) with LCA decreased significantly expression of Sp1 protein in a dose-and time-dependent manner. To further strengthen the effect of LCA on Sp1, we scrutinized expression of Sp1 target proteins such as p21, p27, cyclin D1, Mcl-1 and survivin (9,33,34). The promoter of Sp1 target proteins contains frequent GC-rich sequences and can be regulated by Sp1 protein (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the efforts made to investigate many natural products to find effective chemicals for oral cancers over the last several decades (9), there are currently limited options to treat oral cancer. Even though the frequency of oral cancer is low, the need for effective and selective natural products is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Sp1 might be a good therapeutic molecular target as well as a potential predictor of poor prognosis in cancers. Previous studies found that Sp1 was enhanced in OSCCs, and the downregulation of Sp1 played a role in growth inhibition and induction of apoptosis in oral cancer cells and malignant pleural mesothelioma Jeon et al, 2013;Kim et al, 2013). Also, it was reported that many tumorrelated genes including Bvl-xl, survivin, Bax, and caspase-3 contain Sp1 sites in their promoter region (Black et al, 2001).…”
mentioning
confidence: 97%